MODEL PEMBELAJARAN LEARNING CYCLE 5E TERHADAP PEMECAHAN MASALAH OPERASI HITUNG PADA SEKOLAH DASAR - Ratna Dewi Lestyorini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by the lack of understanding of mathematical problem solving in elementary schools, particularly in arithmetic operations. Mathematics plays a crucial role; everyone, especially in elementary schools, needs to learn and understand basic problem solving in mathematics. Mastery of problem solving is a key indicator of the success of a learning process. Accurate problem solving in every subject matter being studied is essential for children undergoing elementary education. Therefore, to reduce the low problem-solving ability, researchers used the 5E Learning Cycle learning model in learning activities. The purpose of this study was to determine the extent of the influence of the 5E Learning Cycle learning model on elementary school arithmetic problem solving. The approach used in this study was a quantitative approach with a pre-experimental design. The research design applied was a One-Group Pretest-Postest Design. This study examined the effect of the 5E Learning Cycle learning model on elementary school students' arithmetic problem solving, as evidenced by significant increases in scores during the pretest and posttest.